2006
DOI: 10.1097/01.rhu.0000242777.71604.69
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Sensorineural Hearing Loss in Patients With Systemic Lupus Erythematosus

Abstract: If it can be established how often this ASNHL progresses to a clinical problem, it can be important that, as part of initial studies, patients with SLE undergo audiometric tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 37 publications
6
57
0
4
Order By: Relevance
“…Ioannis Kastanioudakis, Nausica Ziavra et al in their clinical study concluded that 1/4th of SLE patients in their study had SNHL in mid and high frequencies and this was a lower percentage when compared to other authors. (28) Roverano S, Cassano G, et al in a clinical study to evaluate SNHL in SLE patients found that 70% of the patients had HL and 66% had sensory neural loss at higher frequency bilateral and symmetrical. No correlation was found between SLE activity and hearing loss.…”
Section: Methodsmentioning
confidence: 98%
“…Ioannis Kastanioudakis, Nausica Ziavra et al in their clinical study concluded that 1/4th of SLE patients in their study had SNHL in mid and high frequencies and this was a lower percentage when compared to other authors. (28) Roverano S, Cassano G, et al in a clinical study to evaluate SNHL in SLE patients found that 70% of the patients had HL and 66% had sensory neural loss at higher frequency bilateral and symmetrical. No correlation was found between SLE activity and hearing loss.…”
Section: Methodsmentioning
confidence: 98%
“…When the oculomotor, trochlear and abducent nerves are involved, myasthenia gravis should be ruled out. Different mechanisms have been proposed such as vasculitis secondary to SLE, microinfarction of the capillaries or arterioles in the temporal bone, and thrombosis in the otologic region 56 . Autoimmune sensory neural hearing loss in SLE is associated with a poor prognosis.…”
Section: Cranial Neuropathiesmentioning
confidence: 99%
“…Hal ini dibuktikan oleh Roverano dkk. 6 di Santa Fe, Argentina yang melakukan penelitian pada 30 wanita LES yang pada saat itu tidak mengeluh gangguan dengar atau riwayat penyakit telinga pada keluarga, ternyata pada pemeriksaan audiometri 20 pasien menunjukkan gangguan dengar sensorineural pada frekuensi tinggi, bilateral, dan simetris.…”
Section: Pendahuluanunclassified